2006
DOI: 10.1007/s00056-006-0626-5
|View full text |Cite
|
Sign up to set email alerts
|

Disc-condyle Relationships during Class II Treatment with the Functional Mandibular Advancer (FMA)

Abstract: Functional jaw orthopedics for correction of skeletal Class II with the rigid fixed FMA leads to side-effects reflected in the disc-condyle relationship in the temporomandibular joints: no adverse effects were observed in joints presenting an initial physiological disc-condyle relationship, whereas the disc position may improve in joints with initial partial or total anterior disc displacement. In comparison with the baseline findings, we observed no post-treatment restriction in the extent of maximum mouth op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 39 publications
(56 reference statements)
5
16
0
Order By: Relevance
“…. Finally, 14 papers fulfilled the inclusion criteria of our review . The remaining five articles from this final selection stage were excluded for the following reasons: The MRI evaluation of the TMJ condition was performed after treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…. Finally, 14 papers fulfilled the inclusion criteria of our review . The remaining five articles from this final selection stage were excluded for the following reasons: The MRI evaluation of the TMJ condition was performed after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Included studies consisted of cohort groups of adolescent patients with class II malocclusions. Twelve articles reported the changes in TMJ articular tissues as demonstrated in MRI . One article used CT scan images to evaluate the volume of the condyle and glenoid fossa, while another used co‐registered serial CBCT images to assess TMJ osseous structure changes.…”
Section: Resultsmentioning
confidence: 99%
“…Watted et al (27) and Kinzinger et al (28) studied 15 patients. The study with the largest sample size was Baltromejus et al (5), with 138 cases.…”
Section: Discussionmentioning
confidence: 99%
“…6,9,[19][20][21][22] The systematic literature review shows that the correct occlusal relationship between the teeth did not cause a change in the physiological position of the condyles and articular discs in TMJ when MRI and CT were examined, 19,21,22 whereas in some cases of TMD an improvement can be obtained as a result of orthodontic treatment. 9,19,22 Some studies found changes in condylar position 3 and in the volumes of the anterior and posterior joint spaces 3,23 due to applied orthodontic mechanics. Furthermore, the use of the chincup caused a morphological change in condylar growth, which may be associated with correction of skeletal malocclusion in conjunction with remodeling in the jaw, 12 as well as the Herbst appliance.…”
mentioning
confidence: 99%
“…Elastics mechanics, 6,23 headgear, 6 rapid maxillary expansion, 1,2 Frankel functional appliance, 9 Bionator, 30 fixed functional orthopedic appliances, 20,21,22 Twin Block 30 and functional mandibular advancement appliance 19 did not cause physiological changes in the positioning of the condyle and articular disc, whereas the implementation or not of extraction protocols did not change this situation. 6,23 Great provider of scientific evidence, randomized clinical trials were found in low number in this systematic review: only two studies.…”
mentioning
confidence: 99%